A pragmatic approach to measuring adherence in treatment delivery in psychotherapy. Issue 5 (2nd September 2020) - Serfaty, Marc; Shafran, Roz; Vickerstaff, Victoria; Aspden, Trefor
ABSTRACT: Measuring therapists' adherence to treatment manuals is recommended for evaluating treatment integrity, yet ways to do this are poorly defined, time consuming, and costly. The aims of the study were to develop a Therapy Component Checklist (TCC) to measure adherence to manualised CBT; to test its application in research and clinical practice; to determine its validity; and consider its cost benefits. We conducted a randomised trial in 230 people with cancer evaluating effectiveness of CBT for depression. In this, therapists delivered manualised treatment. Experts agreed on key components of therapy and therapists were asked to record these after therapy sessions by ticking a TCC. Inter-rater reliability was tested using an independent rater. Therapists delivered 543 CBT sessions. TCCs were completed in 293, of which 39 were assessed by the independent rater. Self-reported TCC data suggested close adherence to the manual. Prevalence-adjusted and bias-adjusted kappa scores suggested substantial agreement, (>0.60) in 38 out of 46 items. Self-rating of adherence saved around £96 per rating. In conclusion the TCC provides a quick and cost effective way of evaluating the components of therapy delivered. This approach could be applied to other psychological treatments and may help with linking therapeutic interventions with outcome.